Effectiveness of the SmartShield for knowledge on sexual abuse prevention among primary school children in Malaysia: A quasi-experimental study - Mohamad Najib Mat Pa; Mohd Noor Norhayati; Zaharah Sulaiman; Nik Hazlina Nik Hussain; Azizah Othman; Azliana Aziz (PLoS ONE, 2025)
Child sexual abuse is a significant public health issue with long-term psychological, physical, and social consequences. Despite increasing awareness, its prevention remains underrepresented in the Malaysian primary school curriculum. The SmartShield program was developed as a culturally relevant, age-appropriate, and video-based intervention to improve sexual education knowledge among primary school children. A quasi-experimental controlled trial was conducted using stratified multistage cluster sampling. Six government primary schools were randomly selected from five regions. In each school, one class from the lower and one from the upper primary were chosen. The sample size was estimated by comparing two means. The SmartShield intervention consisted of two modules per age group and was delivered through 20-minute video-guided sessions. Knowledge was assessed at baseline, post-Module 1 (Week 2), and post-Module 2 (Week 4) using validated questionnaires. Data were analyzed using repeated measures ANOVA, adjusting for sex and region. A total of 881 children for each lower and upper primary student were recruited. The intervention group showed significantly greater improvements in knowledge scores compared to the control group across all modules and time points (p < .001). Among lower primary students, adjusted mean scores increased from 78.5% to 97.1% in the intervention group versus 80.1% to 90.3% in the control group. Among upper primary students, knowledge scores rose from 79.5% to 97.8% in the intervention group, compared to 77.6% to 95.1% in the control group. The SmartShield program was effective in enhancing child sexual abuse knowledge among Malaysian primary school children.